A Comparative Analysis of Physiological and Psychological Effects of Exercising in Indoor Versus Outdoor Environments: Implications for Mood, Motivation, Perceived Exertion, and Exercise Program Adherence on Rori Hotel Gym Clients, Hawassa - Dessalegn, Abera (ETHIOPIAN JOURNAL OF SPORT SCIENCE, 2023)
The purpose of this study was to investigate the differential impacts of indoor and outdoor exercise environments on the physiological and psychological responses of Rori Hotel gym clients in Hawassa, with a focus on mood, motivation, perceived exertion, and exercise program adherence. The research employs a comparative analysis methodology, utilizing both quantitative measures and qualitative assessments. Participants engaged in exercise sessions both indoors and outdoors, with physiological parameters such as heart rate, blood pressure, and oxygen saturation being monitored. Additionally, self-reported measures including mood, motivation levels, perceived exertion, and adherence to exercise programs were recorded through standardized questionnaires and interviews. Preliminary findings suggest that exercising in outdoor environments elicits a significantly more positive effect on mood and motivation compared to indoor exercise. Moreover, participants reported lower perceived exertion levels during outdoor sessions, indicating a potentially greater enjoyment of the activity. Physiological responses, while varied, indicate a trend towards increased oxygen saturation and lower heart rates during outdoor exercise. These results have important implications for designing exercise programs tailored to the preferences and needs of Rori Hotel gym clients in Hawassa. By incorporating outdoor exercise opportunities, hotel management can potentially enhance client satisfaction, motivation, and adherence to fitness routines. Further research is recommended to explore long-term effects and specific demographic influences on these findings.